Induced Microphase Separation in Hybrid Composite Polymer Electrolytes Based on Poly(acrylonitrile‐r‐butadienes) and Ionic Liquids. Issue 6 (18th February 2016) - Wirey, Michael; Hunt, Marcus; Blensdorf, Tyler; Stein, Barry D.; Werner‐Zwanziger, Ulrike; Hanson, Margaret A.; Mahmoud, Waleed E.; Al‐Ghamdi, Ahmed A.; Carini, John; Bronstein, Lyudmila M.
Abstract : Novel hybrid, composite polymer electrolytes (HCPEs) based on poly(acrylonitrile‐ r ‐butadiene) (PAN‐ r ‐PB), CN‐modified silica nanoparticles (CN‐MSNs), Li triflate, and ionic liquids (ILs) are synthesized. Using a combination of methods, it is demonstrated that these materials segregate into PAN‐rich and PB‐rich phases, the behavior of which changes depending on the IL type. The incorporation of ILs containing hexyl and octyl substituents at the imidazolium rings leads to a higher mobility of the PB‐rich phase and a decrease of the density of the neighboring PAN‐rich phase, allowing an improvement of the Li ion conductivity. However, with an increase of the substituent length from decyl to dodecyl, ordering of the hydrophobic tails in the PB‐rich phase leads to both stiffening of the latter and corresponding ordering of the ionic pairs of ILs, resulting in a decreased conductivity. The results of this work are broadly applicable for controlling the structure and properties of polymeric materials exhibiting microphase segregation. Abstract : It is demonstrated that polymer electrolytes based on poly(acrylonitrile‐ r ‐butadiene) (PAN‐ r ‐PB), CN‐modified silica particles, Li triflate, and ionic liquids (ILs) segregate into PAN‐rich and PB‐rich phases. The ILs containing hexyl and octyl tails lead to a higher mobility of the PB‐rich phase and a decrease of the density of the PAN‐rich phase, allowing the Li ion conductivity improvement.